CSE/H2S ameliorates colitis in mice via protection of enteric glial cells and inhibition of the RhoA/ROCK pathway - Wang, Song; Ding, Yanyu; Jiang, Wenjun (Frontiers in Immunology, 2022)
The enteric glial cells (EGCs) participate in the homeostasis of the gastrointestinal tract, and RhoA/ROCK signaling pathway plays a vital role in colonic tight junctions. Hydrogen sulfide (H2S) has been reported to alleviate colitis. However, the effect and mechanism of endogenous H2S on colitis remain unclear. This study established a Cystathionine-γ-lyase (CSE) knockout mouse model, a significant source of H2S production in the gut. The role of CSE-produced H2S on EGCs and the RhoA/ROCK signaling pathway was investigated in experimental colitis using CSE knockout (KO) and wild-type (WT) mice. CSE gene knockout animals presented with disease progression, more deteriorated clinical scores, colon shortening, and histological damage. EGCs dysfunction, characterized by decreased expression of the glial fibrillary acidic protein (GFAP), C3, and S100A10, was observed in the colon of WT and KO mice, especially in KO mice. RhoA/ROCK pathway was significantly upregulated in colon of colitis mice, which was more evident in KO mice. Pretreatment with NaHS, an exogenous H2S donor, significantly ameliorated mucosal injury and inhibited the expression of proinflammatory factors. Furthermore, we found that NaHS promoted the transformation of EGCs from “A1” to “A2” type, with decreased expression of C3 and increased expression of S100A10. These findings suggest that CSE/H2S protects mice from colon inflammation, which may be associated with preserving EGCs function by promoting EGCs transformation and inhibiting the RhoA/ROCK pathway.